2007
DOI: 10.1186/1472-6882-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medical therapy utilization by people with chronic fatiguing illnesses in the United States

Abstract: Background: Chronic fatiguing illnesses, including chronic fatigue syndrome (CFS), pose a diagnostic and therapeutic challenge. Previous clinical reports addressed the utilization of health care provided to patients with CFS by a variety of practitioners with other than allopathic training, but did not examine the spectrum of complementary and alternative medicine (CAM) therapies used. This study was designed to measure CAM therapy use by persons with fatiguing illnesses in the United States population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…Recently, the United States has seen an upward trend in the use of nonconventional medicine for chronic conditions, [19][20][21][22] mimicking trends seen internationally. [23][24][25] Although many studies have examined the use of complementary and alternative medicine (CAM) within different chronic disease populations, 16,26,27 researchers also suggest that the reasons for CAM use for chronic back or neck pain and other musculoskeletal diseases warrant further study.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, the United States has seen an upward trend in the use of nonconventional medicine for chronic conditions, [19][20][21][22] mimicking trends seen internationally. [23][24][25] Although many studies have examined the use of complementary and alternative medicine (CAM) within different chronic disease populations, 16,26,27 researchers also suggest that the reasons for CAM use for chronic back or neck pain and other musculoskeletal diseases warrant further study.…”
Section: Introductionmentioning
confidence: 91%
“…Accordingly, chronic fatigue is one of the most common complaints treated by alternative complementary therapies in the United States. 3 In this study, the antifatigue effect of moxibustion on 44 subjects with ICF was investigated. This study was not targeted toward CFS, which can be diagnosed by typical criteria and has more severe symptoms than those of ICF.…”
Section: Discussionmentioning
confidence: 99%
“…2 Thus, patients suffering from ICF or CFS frequently use alternative and complementary therapies. 3,4 Traditional Oriental medicine considers chronic fatigue to be the result of an unbalanced state among interfunctioning organs, or a deficient vital energy (called qi) condition with characteristic blood symptoms. 5 Several clinical studies have shown positive results of herbal remedies on CFS, [6][7][8] and acupuncture and moxibustion therapy have been leading treatments in traditional Oriental medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these patients use complementary and alternative medicine (CAM) [10][11][12]. A study of fibromyalgia patients in the U.S. found that 92.6 % of the participants (mostly women) reported to have used some kind of CAM [10].…”
Section: Introductionmentioning
confidence: 99%